2021
DOI: 10.1111/1471-0528.16848
|View full text |Cite
|
Sign up to set email alerts
|

The role of obesity on urinary incontinence and anal incontinence in women: a review

Abstract: Obesity prevalence is increasing worldwide, with significant healthcare implications. We searched PubMed/MEDLINE, Embase and the Cochrane Library for articles registered until June 2020 to explore the relationship between obesity and urinary (UI) and anal incontinence (AI). Obesity is associated with low‐grade, systemic inflammation and proinflammatory cytokine release, producing reactive oxygen species and oxidative stress. This alters collagen metabolism and, in combination with increased intra‐abdominal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 74 publications
1
18
0
2
Order By: Relevance
“…As expected, our study found that in the case of UI, a strong association existed between advanced age, postmenopausal status, and obesity, which has been reported previously [ 6 8 , 10 , 11 ]. Obesity leads to a continuous increase in intra-abdominal pressure, which may result in weakness of the pelvic floor muscles and a subsequent elevated risk of UI [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, our study found that in the case of UI, a strong association existed between advanced age, postmenopausal status, and obesity, which has been reported previously [ 6 8 , 10 , 11 ]. Obesity leads to a continuous increase in intra-abdominal pressure, which may result in weakness of the pelvic floor muscles and a subsequent elevated risk of UI [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, BMI was found as another associated risk factor for CI, in line with studies which also have shown this relationship ( 8 10 , 22 ). Indeed, obesity is a known risk factor for UI, and the pathophysiological mechanism has been explained by the negative effects of chronic increased intra-abdominal pressure and oxidative stress from visceral adipose on the collagen content and supportive neuromuscular structures of the pelvic floor ( 27 ). However, there are also studies reporting no association ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index has been linked to intra-abdominal pressure and intravesical pressure, which overcomes urethral closing pressure and leads to incontinence [ 44 ]. In addition, oxidative stress from visceral adipose tissue is likely to have a negative effect on the collagen and supportive structures of the pelvic floor, which confer continence [ 45 ]. Our meta-analysis indicates that these three factors are associated with UI among CrossFit practitioners.…”
Section: Discussionmentioning
confidence: 99%